The Staggering Indian Industry: Is Finance Responsible? The Changing Role of Finance in the Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The paper is based on the work done under UGC sponsored major research project. It provides a sectoral analysis of the role of financial advancement in the growth of the real sectors of the economy. Using unit root testing, the techniques of Granger causality, and vector autoregressive model, it investigates the relationship between an increase in bank credit and industrial growth in India for the time period 2007-2013. It is found, using monthly data, that in recent years the increasing bank credit neither promotes the growth of the industrial sector, nor the service sector. The financial sector has been responding positively to the demands of the growing real sector. The growth of the Indian economy is thus not a case of finance-led growth any longer. This being so there should be no hesitation on the side of policymakers to pursue restrictive monetary policies to control inflation. The neglected informal sector of the economy needs to be brought into the ambient of bank finance. This could help promote growth.